P002 How do glycans affect immune cells in rheumatoid arthritis?. (21st February 2018) - Molhoek, A; Hafkenscheid, L; Toes, R; van Vliet, S; van Kooyk, Y
Abstract : Introduction: Anti-Citrullinated Protein Antibodies (ACPAs) are specific for Rheumatoid Arthritis (RA) and have been implicated in disease pathogenesis. The fragment antigen-binding domain (Fab) of ACPA was recently shown to be extensively glycosylated. 1 It is known that glycans play a key role in controlling innate and adaptive immunity, 2 however to date there is limited understanding on the mode of action of glycans in RA. We hypothesise that the glycans on ACPA interact with glycan binding receptors and thus modulate immune responses in RA. Therefore, our aim is to elucidate the glycan effect of ACPA and other glycans on immune cells of RA patients to increase our understanding of RA pathogenesis. Methods: A whole blood flow assay was used to study glycan interactions with leukocytes. Leukocytes were isolated from blood and cells were incubated for 2 hours at 4°C with 15 µg/ml highly glycosylated ACPA and immunomodulatory glycoconjugates, such as sialic acid, Lewis-x, Lewis-y, mannose and as a negative control GlcNac. Glycan binding and identification of immune cell subsets was assessed with flow cytometry using a whole blood flow antibody panel. Results: This study examined the glycan-binding capacity of leukocytes in healthy donors via the whole blood flow assay. B cells appear to be superior in their interaction capacity with a variety of glycans, including the Fab glycan on APCA. This is an important finding because B cells play a key role in the pathogenesis of RA, through their antigen presenting capacity as well as their production of ACPA. In future studies RA patients material will be used to assess the glycan binding capacity to immune cell and to elucidate their role in the pathogenesis of RA. Conclusions: This study examined the glycan-binding capacity of leukocytes in healthy donors via the whole blood flow assay. B cells appear to be superior in their interaction capacity with a variety of glycans, including the Fab glycan on APCA. This is an important finding because B cells play a key role in the pathogenesis of RA, through their antigen presenting capacity as well as their production of ACPA. In future studies RA patients material will be used to assess the glycan binding capacity to immune cell and to elucidate their role in the pathogenesis of RA. References: . Rombouts Y. Extensive glycosylation of ACPA-IgG variable domains modulates binding to citrullinated antigens in rheumatoid arthritis. Annals of the rheumatic diseases2016;75(3):578–85. . Johnson L. The regulatory power of glycans and their binding partners in immunity. Trend in Immunology 2013;34(6):290–298. Disclosure of interest: None declared